Pancreatitis During Treatment with Liraglutide - Famularo, Giuseppe; Gasbarrone, Laura; Minisola, Giovanni (JOP. Journal of the Pancreas, 2012)
No abstract available. Image: San Camillo Hospital. Rome, Italy